Over a million students use our free study notes to help them with their homework
Let's remember what applying a modulus to any number actually does. Applying the modulus to a number just gives us back the positive version of that number- if it is positive, we get back itself, and if i...
1) X2 +2Y2= 18 2) X - Y = 3 Rearrange 2) in the form X=3-Y then substitute in to 1); (3-y)2 +2Y2=18, this is your new equation 3 9+3Y+3Y+Y2+2Y2=18 3) 9+6y+3Y2= 18 Divide equation 3) by 3 3 ...
(1) 4x2 + y2 - 25 = 0 (2) y - 2x - 1 = 0 Rearranging (2) into an equation of y in terms of x we have:y = 2x +1now substituting into equation (1) 4x2 + (2x +1)...
2y1/2 -7y1/4+ 3 = 0 We need to use a substitution to obtain a quadratic.Let y1/4 = x (use the y with the smallest fractional power as your substitution)From this, we can s...
The product rule states that if y=uv, where u and v are both functions of x, then dy/dx = u(dv/dx) + v(du/dx)Therefore, the differential of 2xe3...
←
642
643
644
645
646
→
Internet Safety
Payment Security
Cyber
Essentials